Penerapan Punishment Sebagai Upaya Pembentukan Prilaku Disiplin Sholat Berjamaah Santri Putri Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan - Heni Lestari; Suci Hartati; Miftahul Anwar (Journal on Education, 2024)
This exploration expects to portray the use of discipline as a work to shape petitioning God discipline conduct among the understudy gathering at the Hidayatul Mubtadiin Islamic Life experience School in Jati Agung, South Lampung. This exploration is a subjective distinct examination, specifically the data gathered is as modified structures, individualized associations, pictures, not numbers. Wellsprings of data come from basis data sources, auxiliary data. The data assortment strategies utilized in this exploration are perception, meetings and documentation. In this examination, the legitimacy of the data utilized is triangulation. Exercises in data examination are: data decrease, data show, and making determinations/confirmation. In light of the exploration results, the accompanying ends can be drawn: The utilization of discipline as a work to frame trained supplication conduct in the gathering of female understudies at the Hidayatul Mubtadiin Islamic Life experience School incorporates directing effort to new understudies with respect to the principles and disciplines. , the utilization of discipline utilizes a progressive framework, and the execution of discipline will be followed up. by Jam'iyah area coordinators and security area coordinators. The discipline applied in training female understudies in regards to congregational petitions to heaven is as actual discipline, to be specific being drenched with squander water, and standing up while perusing the Tafsir after sunrise and non-actual discipline, in particular as a censure. The use of this discipline has a positive effect in training female understudies in congregational supplications. The supporting variables are things that empower the cycle to continue as per plans and goals, including the immovability of the Jam'iyah the executives and security area heads, the administration being reliable in distributing disciplines, and furthermore upheld by the shortfall of petitions and feminine report sheets. What's more, the repressing variables are understudies who will be rebuffed for being debilitated, resistance among understudies and chairmen, absence of assessment and absence of consistency in administration.